New cockroach species of the genus Panchlora Burmeister (Blaberidae, Panchlorinae) from Ecuador - Vidlička, Ľubomír (Zootaxa, 2016)
The genus Panchlora includes 49 species, but only 45 are widely distributed in Central and South America. Most of them are green. The new species herein described presents an ornamental coloration markedly different of all until now described species. Panchlora kozaneki sp. n. is similar to Panchlora pulchella Burmeister, 1838. The number of species known from Ecuador is increased to eight.